PENGGANTIAN NAZHIR WAKAF PERSEORANGAN KE BADAN HUKUM DALAM PERSPEKTIF MAQASHID ASY-SYARI’AH (Studi di Badan Wakaf Indonesia Perwakilan Kota Tasikmalaya) - Acep Zoni SM (Universitas Siliwangi, 2020)
Abstract The study aims at examining how the replacement of Nazaf waqf from individual Nazar to legal entity Nazar in the perspective of Maqashid ash-Shari'ah. The method used is normative research containing empirical elements with a qualitative approach. Source of data comes from reference data (library) and the results of field studies and interviews with various parties (fields) located in the City of Tasikmalaya. The results of this study are the replacement of individual nazhir to legal body referring to the public benefit, namely the control of waqf assets owned by the legal body. Besides, it constitutes the spirit to realize the objectives of maqashid asy-syari'ah waqf itself. From the perspective of maqashid al-shari'ah, the replacement of waqf from individuals to legal body is to realize the objectives of waqf in accordance with Shari'a (hifz ad-din), improve the professionalism of Nazir persons (hifdz an-nafs), perpetuate the benefits of waqf and improve the economy (hifz al-mal). Keywords: nazhir, waqf, maqashid ash-shari’ah AbstrakStudi ini bertujuan untuk mengkaji bagaimana penggantian nazhir wakaf dari nazhir perseorangan ke nazhir badan hukum dalam perspektif maqashid asy-syari’ah. Metode yang digunakan dalam studi ini adalah penelitian normatif yang mengandung elemen empiris dengan pendekatan kualitatif. Sumber data berasal dari data referensi (library) dan hasil studi lapangan serta wawancara dengan berbagai pihak (field) yang berlokasi di Kota Tasikmalaya. Hasil studi ini adalah penggantian nazhir perseorangan kepada badan hukum mengacu kepada kemaslahatan umum yaitu penertiban aset wakaf yang dimiliki oleh badan hukum itu sendiri selain hal itu merupakan semangat untuk mewujudkan tujuan maqashid asy-syari’ah wakaf itu sendiri. Dari perspektif maqashid asy-syari’ah, penggantian nazhir wakaf dari perseorangan ke badan hukum adalah untuk mewujudkan tujuan wakaf sesuai syariat (hifz ad-din), meningkatkan profesionalitas person nazhir (hifz an-nafs), dan mengabadikan manfaat wakaf dan meningkatkan perekonomian (hifz al-mal). Kata Kunci: nazhir, wakaf, maqashid asy-syari’ah